Epidermal cyst of the mandible: a case report. (22nd November 2016) - Thomas, M.; Tremain, R.; Laugharne, D.
Abstract: We present a case of epidermal cyst affecting left body of the mandible. The reported incidence of epidermal cyst in the oral cavity is 1.6%, with floor of the mouth being the most common site. There are 16 reported cases of epidermal cysts in the mandible; of these four were post‐traumatic inclusion cysts.